Service Qualities Affecting Customer Satisfaction in “A-Lan Noodle Restaurant” - Vaichayee, Tanapol; Sawang, Sumalee (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this study were 1) to examine the A-Lan Noodle Restaurant’s levels of service quality, 2) to evaluate the levels of customer satisfaction, 3) to compare levels of service quality classified by demographic factors, and 4) to study the service quality of “A-Lan Noodle Shop” that affect customer satisfaction. The data was gathered from a sample of 400 customers. Collecting data by using a questionnaire and analyzing by percentage, frequency, mean, standard deviation, independent t-test, One-way ANOVA, pairwise differences test using the method of LSD, and simple regression analysis. The results showed that 1) The customers had opinions on the service quality of “A-Lan Noodle Shop” overall at the highest level (mean=4.40, SD=0.49). The aspect with the highest mean was service reliability (mean=4.50, SD=0.44), followed by customer confidence (mean=4.45, SD=0.40), and the lowest was sympathy for customers (mean=4.32, SD=0.66). 2) Most of the respondents were satisfied with the services of A-Lan Noodle Shop. Overall, it was at the highest level (mean=4.36, SD=0.79). 3) Demographic factors of different A-Lan Noodle Shop customers had different opinions on levels of service quality with a statistically significant difference at .05. And 4) The service quality of “A-Lan Noodle Shop” affected satisfaction with a statistically significant difference at .05 (R2=0.880).